2018
DOI: 10.1088/2051-672x/aac1a2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of steel disc surface texture in contact with ceramic ball on friction and wear in dry fretting

Abstract: Ceramics are used in a wide range of applications including bearings. Ceramic-metal contacts are of great potential for the future. The purpose of this paper is to study the effect of a surface topography of a steel disc in contact with ceramic ball on friction and wear under dry gross fretting regime. Experiments were carried out using an Optimol SRV5 tribological tester under dry friction conditions in the gross fretting regime. The number of cycles was set to 18000, temperature was 30 °C, the stroke was set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Wear of disc was substantially higher than wear of balls. Similar results were obtained in the other tests [26].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Wear of disc was substantially higher than wear of balls. Similar results were obtained in the other tests [26].…”
Section: Resultssupporting
confidence: 91%
“…Experiments were carried out under dry-friction conditions using Optimol SRV5 tribotester (Optimol Instruments Prüftechnik GmbH, Munich, Germany) in a ball-on-flat configuration. This tester was previously used in other fretting tests [26,27]. The displacement of a ball was measured by an inductive displacement sensor which was mounted next to the oscillating module ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most of the papers, only R q , R sk , R ku or its 3D equivalent topography parameters have been reported. Recently, Lenart et al [20] showed that there are other topography parameters which also vary significantly during fretting wear. Sedlaček et al [28] showed a correlation between skewness, kurtosis and tribological behavior of contacting surfaces.…”
Section: Variation Of Topography Parameters With Sliding Time For Friction Testsmentioning
confidence: 99%
“…An increase in the surface roughness height led to improved wear resistance. The authors of [41] investigated the influence of the surface texture of steel discs contacting ceramic balls on the tribological performance of the sliding assembly in a dry gross sliding fretting regime and found that the results were better for lower disc roughness heights. The influence of disc surface texturing on dry gross sliding fretting of a ball-on-disc assembly was investigated [42].…”
Section: Introductionmentioning
confidence: 99%